Child Abuse Syndrome - Monka Turska; Michał Raban; Cezary Grochowski; Beata Kulik-Rechberger (Kazimierz Wielki University, 2017)
According to WHO, child abuse is defined as "any intentional or unintended action towards a person under the age of 18 that negatively affects the present or future health, experience, physical and psychosocial development of a child". There are four main types of child abuse: physical, mental, sexual, and negligence, understood as the failure of taking care of a child. The accountable diagnosis of a battered child syndrome requires the knowledge of clinical symptoms and risk factors. The ascertainment or suspicion of this syndrome requires reporting to the competent authorities in accordance with the applicable procedures.